2020
DOI: 10.1186/s13041-020-00704-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered striatal dopamine levels in Parkinson’s disease VPS35 D620N mutant transgenic aged mice

Abstract: Vacuolar protein sorting 35 (VPS35) is a major component of the retromer complex that mediates the retrograde transport of cargo proteins from endosomes to the trans-Golgi network. Mutations such as D620N in the VPS35 gene have been identified in patients with autosomal dominant Parkinson’s disease (PD). However, it remains poorly understood whether and how VPS35 deficiency or mutation contributes to PD pathogenesis; specifically, the studies that have examined VPS35 thus far have differed in results and metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Vanan et al used a Rosa26‐based transgene expression platform to generate a VPS35 D620N mouse model. The study found that the dopamine level of VPS35 D620N mice was significantly higher than that of nontransgenic control mice 41 …”
Section: Vps35 and The Pathogenesis Of Pdmentioning
confidence: 86%
See 1 more Smart Citation
“…Vanan et al used a Rosa26‐based transgene expression platform to generate a VPS35 D620N mouse model. The study found that the dopamine level of VPS35 D620N mice was significantly higher than that of nontransgenic control mice 41 …”
Section: Vps35 and The Pathogenesis Of Pdmentioning
confidence: 86%
“…The study found that the dopamine level of VPS35 D620N mice was significantly higher than that of nontransgenic control mice. 41 F I G U R E 1 Cellular processes affected by the VPS35 mutation. VPS35, which is the core component of the retromer, along with VPS26 and VPS29, sits at the endosomal membrane and recognizes cargo to be sorted.…”
Section: Vps35 and The Dopamine Signaling Pathwaymentioning
confidence: 99%
“…The mixture of mobile phase was 0.01% EDTA (adjusted to pH 4.0, 100% acetic acid), 2% methanol (v/v), and 7% acetonitrile (v/v). All solutions for HPLC analysis were double filtered through 0.2 μm membranes and degassed before use as described previously [ 34 ]. The flow rate of mobile phase was 0.8 ml per minute and UV detector was set at 340 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The flow rate of mobile phase was 0.8 ml per minute and UV detector was set at 340 nm. The final dopamine level was represented as μg/mg of brain tissue [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on these results, genetically engineered animal models harboring D620N VPS35 have been created, and they have variable phenotypes. In a viral-mediated gene transfer rat model, the expression of human D620N VPS35 in the SNpc resulted in prominent dopaminergic neuron loss with axonal pathology, whereas D620N VPS35 Tg aged mice generated via Rosa26-based transgenesis did not exhibit apparent motor impairment or neurodegeneration (Tsika et al, 2014;Vanan et al, 2020). On the contrary, Tg flies expressing human D620N VPS35 or P316S VPS35 displayed a detrimental phenotype including dopaminergic neuron loss, locomotor dysfunction, a shortened lifespan, and susceptibility toward PD-linked environmental toxins (Wang et al, 2014).…”
Section: Molecular and Cellular Mechanisms Underlying Familial Parkin...mentioning
confidence: 99%